Enhancing Students' Learning Outcomes in Chemistry Learning Through Assessment for Learning - Fitria, Maulida Rizki; Muchlis, Muchlis (Universitas Islam Indonesia, 2026)
Continuous monitoring of student understanding is crucial because the nature of complex redox reaction materials is one of the primary causes of suboptimal student achievement. This research aims to enhance student learning outcomes through an assessment for learning approach that integrates feedback on an ongoing basis. This investigation employed a pre-experimental one-group pretest-posttest methodology with 36 twelfth-grade learners from one of Surabaya's high schools. The results showed a significant improvement in student learning outcomes, with the average score increasing from 37.22 to 86.04. The average N-gain reached 0.77, indicating high growth in learning achievement, with 88.89% of students attaining the high category. The results of this study show that using assessment for learning, which includes defining learning objectives, creating useful classroom discussions and assignments as evidence of student comprehension, giving continuous feedback, and including students as owners of their own learning process, is effective in improving students’ learning outcomes and has a measurable positive impact on concept mastery. These findings suggest that the assessment for learning approach is effective for improving students' understanding of complex topics such as redox reactions.